2013
DOI: 10.1021/ef401562w
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of the Impact of Steam on Polyethyleneimine on Silica for CO2 Capture

Abstract: An amine sorbent, prepared by impregnation of polyethyleneimine on silica, was tested for steam stability. The stability of the sorbent was investigated in a fixed bed reactor using multiple steam cycles of 90 vol % H2O/He at 105 °C, and the gas effluent was monitored with a mass spectrometer. CO2 uptake of sorbent was found to decrease with repeated exposure to steam. Characterization of the spent sorbent using N2 physisorption, SEM, and thermogravimetric analysis (TGA) showed that the decrease in CO2 loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 32 publications
6
82
1
Order By: Relevance
“…However, the presence of water in the process may have an influence on desorption kinetics for some types of supported amine sorbents. 32,49 Further study on the effect of steam in terms of desorption kinetics is required and ongoing.…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of water in the process may have an influence on desorption kinetics for some types of supported amine sorbents. 32,49 Further study on the effect of steam in terms of desorption kinetics is required and ongoing.…”
Section: Resultsmentioning
confidence: 99%
“…[21] The alumina-supported adsorbent outperformed its SBA-15 counterpartb yawide margin, showing a CO 2 uptake loss of 16.3 %a so pposed to 67.1 %f or SBA-15. [22] studied the steam stability of PEI-impregnated grade G-10 silica (Fuji Silysia Chemical Ltd.) throughe ight consecutivea dsorption/steam regeneration cycles. [21] The authors attributed the poor performance of the impregnatedS BA-15 following exposure to steam to structural collapse or restructuring of the support and amine leaching.…”
Section: Introductionmentioning
confidence: 99%
“…[21] When 400 ppm CO 2 in N 2 was used as adsorbate to mimic direct air capture,t he differencew as even more pronounced, with an uptake loss of 25.2 %f or the former support relative to 81.3 %f or the latter one. [22] Ruling out the first four factorst hrough as eries of experiments,t he authors speculated that amine reagglomeration on the silica support might have been the reason. As no significant change in amine loading was observed following exposure to steam, the authors suggested that the amine might have leachedo ut of the pores, coveringt he external surface of the support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4(a), (b)), the adsorption peaks at 3349 cm −1 , 3284 cm −1 and 914 cm −1 were assigned to the asymmetric bending and stretching vibration of Si-OH, which is the main structure in the GF substrate. In comparison to the GF, the PEI-loaded GF exhibited new peaks located at 2945 cm −1 (symmetric stretching of -CH 2 -), 2837 cm −1 (asymmetric stretching of -CH 2 -) and 1671 cm −1 (bending vibration of -N(R)H), which indicated that PEI were successfully introduced [39]. The spectra of the PEI-loaded GF before ( Fig.…”
Section: Ft-ir Spectroscopymentioning
confidence: 92%